TANGGUNG JAWAB TERBATAS INDUK PERUSAHAAN BUMN TERHADAP ANAK PERUSAHAAN BUMN PRA DAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 01/PHPU-PRES/XVII/2019 TAHUN 2019 - Tina Amelia (SOL JUSTICIA, 2020)
Status of BUMN Subsidiaries in Supreme Court Decision No. 21 / HUM / 2017 states that the status of BUMN subsidiaries is BUMN. However, with the Constitutional Court Decision Number 01 / PHPU-PRES / XVII / 2019 which confirms that BUMN subsidiaries do not have BUMN status resulting in a mismatch between das sein (in fact) and das sollen (should be), where in fact from the operational point of view the subsidiary is still very reflects the involvement of its parent company as a BUMN, and this will also affect the parent company accountability system for BUMN subsidiaries in the concept of Limited Liabilities. This research uses a normative legal research method with a normative - empirical approach, and in carrying out the analysis not only normative-qualitative, but first makes an effort to establish criteria for identification, classification and systematization and comes to legal discovery whether in the form of legal interpretation or construction. law to give birth to a legal argument